The medium-sized cities working as smart city - Machado Maia, Claudio (2022)
Analyzing a city from its functions, as a smart city in consideration of its innovative medium, presupposes its protagonist of regional influence. In the debate about the complexity of interactions between city functions and social participation, this article aims to reflect suggestive characteristics and categories of analysis, as a source of inquiry that highlights the smart city. The methodology is based on the exploratory research, presenting a bibliographical review of the role of cities in the new economy, using data and bibliographical information, together with research materials, presentations and publications of the theme. Textual production results in a roadmap in the form of an array of elements, contexts and categories of analysis, allowing an understanding of the importance of cities, such as smart regions, playing an important role in the regional configuration.